Pengaruh Kinerja Keuangan Dan Makroekonomi Terhadap Harga Saham Sektor Industri Konsumsi - Nur Muflihatun Azizah; Lukytawati Anggraeni; Tony Irawan (Jurnal Ekonomi, 2020)
The stock price can be affected by financial performance and macroeconomic. Investors need to consider financial performance and macroeconomic conditions in making an investment decision. The goal of this study is to analyze the effect of financial performance and macroeconomics on the stock price of the consumer goods industry. Panel Data Regression is used in this study to analyze the effect of financial performance and macroeconomic on the stock price. The result of this study shows the liquidity ratio (CR) has a significant and negative effect on stock price, while the profitability ratio (ROE) has a significant and positive effect on the stock price. Macroeconomic inflation and exchange rate have a significant and positive effect on the stock price. Firms with a high liquidity ratio (CR) have to control the liquidity ratio because in the long term high liquidity has a negative effect on stock price so the stock price may decrease. Investors need to compare the financial performance in order to make a good decision.